2013
DOI: 10.1101/cshperspect.a012716
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Sensing by the ATM and ATR Kinases

Abstract: In eukaryotic cells, maintenance of genomic stability relies on the coordinated action of a network of cellular processes, including DNA replication, DNA repair, cell-cycle progression, and others. The DNA damage response (DDR) signaling pathway orchestrated by the ATM and ATR kinases is the central regulator of this network in response to DNA damage. Both ATM and ATR are activated by DNA damage and DNA replication stress, but their DNAdamage specificities are distinct and their functions are not redundant. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
953
1
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,197 publications
(980 citation statements)
references
References 155 publications
(164 reference statements)
16
953
1
10
Order By: Relevance
“…CHK-1 is phosphorylated and activated by the ATR (ATL-1 in C. elegans) protein kinase during a DNA damage response, and this is an evolutionarily conserved response found in organisms ranging from yeast to man. 12 Using antibodies that recognize the phosphorylated and activated form of CHK-1, we found that CHK-1 was largely inactive in Z2/Z3 in starved L1s, however after feeding the protein was indeed activated, and activation persisted for about an hour before dissipating. 5 This result suggested that a DNA-based signal was being generated, in a nutrientdependent manner, in Z2/Z3 that Figure 1.…”
Section: Checkpoint Control Of Z2/z3 Cell Cycle Reentrymentioning
confidence: 99%
See 2 more Smart Citations
“…CHK-1 is phosphorylated and activated by the ATR (ATL-1 in C. elegans) protein kinase during a DNA damage response, and this is an evolutionarily conserved response found in organisms ranging from yeast to man. 12 Using antibodies that recognize the phosphorylated and activated form of CHK-1, we found that CHK-1 was largely inactive in Z2/Z3 in starved L1s, however after feeding the protein was indeed activated, and activation persisted for about an hour before dissipating. 5 This result suggested that a DNA-based signal was being generated, in a nutrientdependent manner, in Z2/Z3 that Figure 1.…”
Section: Checkpoint Control Of Z2/z3 Cell Cycle Reentrymentioning
confidence: 99%
“…CHK-1 is part of a DNA-based signaling pathway that triggers cell cycle delay in response to DNA replication stress or DNA DSBs. 12 Under our RNAi conditions, chk-1(RNAi) animals are viable however they are also sterile with high penetrance. We opted to pursue the basis for the sterility phenotype, and observed that chk-1(RNAi) adults showed a complete absence of a germline.…”
Section: Checkpoint Control Of Z2/z3 Cell Cycle Reentrymentioning
confidence: 99%
See 1 more Smart Citation
“…Accompanying the pH2AX was the phosphorylation and, hence, the activation of the ataxia telangiectasia-mutated (ATM) kinase (p-ATM, Fig. 4A), which is known to trigger the cascade of events leading to cell-cycle arrest as the cells attempt DNA repair (23). Sensing DNA damage response, P53 will be phosphorylated and trigger cell-cycle arrest (24).…”
Section: Cell Death Kinetics Induced By Sgn-cd123amentioning
confidence: 99%
“…The DNA damage responsive protein kinase ATR is recruited to the DNA damage by interacting with the RPA coated ssDNA via its regulatory subunit ATRIP. 5 The authors found ATR was recruited to DSBs induced by high LET treatment and this recruitment was significantly decreased in the absence of Exo1.…”
mentioning
confidence: 99%